Search for charged Higgs bosons produced in association with a top quark and decaying via H± → [tau][nu] using pp collision data recorded at √s = 13 TeV by the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Physics letters, 2016)
Charged Higgs bosons produced in association with a single top quark and decaying via H±→τν are searched for with the ATLAS experiment at the LHC, using proton-proton collision data at s=13 TeV corresponding to an integrated luminosity of 3.2 fb−1. The final state is characterised by the presence of a hadronic τ decay and missing transverse momentum, as well as a hadronically decaying top quark, resulting in the absence of high-transverse-momentum electrons and muons. The data are found to be consistent with the expected background from Standard Model processes. A statistical analysis leads to 95% confidence-level upper limits on the production cross section times branching fraction, σ(pp→[b]tH±)×BR(H±→τν), between 1.9 pb and 15 fb, for charged Higgs boson masses ranging from 200 to 2000 GeV. The exclusion limits for this search surpass those obtained with the proton-proton collision data recorded at s=8 TeV.
*The ATLAS Collaboration: M. Aaboud, C.F. Anders, V. Andrei, A.E. Baas, O. Brandt, J.I. Djuvsland, M. Dunford, D.E. Ferreira de Lima, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, V. Radescu, M. Sahinsoy, S. Schaetzel, V. Scharf, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und 2819 weitere Personen]
Im Titel sind die Zeichen "+" und "-" hochgestellt
Im Titel sind [tau] und [nu] als griechische Buchstaben dargestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 19.05.2020